Carbon sink strength of a Mediterranean cork oak understorey: how do semi-deciduous and evergreen shrubs face summer drought? - Correia, A. C.; Costa e Silva, F.; Correia, A. V.; Hussain, M. Z.; Rodrigues, A. D.; David, J. S.; Pereira, J. S. (Journal of Vegetation Science, 2013)
Questions How do semi-deciduous and evergreen shrubs exploit environmental resources during summer drought? What is the contribution of the understorey shrubby layer to ecosystem carbon assimilation? To what extent are carbon balance and transpiration impacted by a rain pulse? Location Cork oak open woodland in the Mediterranean region. Methods We used closed dynamic light and dark chambers to measure gas exchange (CO2 and H2O) in the dominant shrub understorey species Cistus salviifolius, Cistus crispus (semi-deciduous) and Ulex airensis (evergreen), together with plant physiological and morphological measurements during summer drought and autumn recovery. A hyperbolic light response model constrained by vapour pressure deficits was fitted for up-scaling shrub photosynthesis to the ecosystem level. The data were compared, on a daily and daytime basis, with gross primary productivity estimates from ecosystem eddy-covariance flux measurements. Results The onset of summer drought led to a significant leaf area reduction in semi-deciduous species. A general decrease in photosynthesis in all species was observed, while evapotranspiration and above-ground respiration fluxes contrasted among species during summer progression and autumn recovery. The shallow-rooted C. salviifolius was able to use light more efficiently than the other two species, although with poor stomatal control over water loss and consistently higher above-ground respiration rates, leading to lower water and carbon use efficiencies when compared with C. crispus. The deep-rooted shrub U. airensis maintained higher leaf water potentials and very low photosynthetic rates while decreasing transpiration rates throughout the summer drought. A summer rain pulse showed that shallow-rooted shrubs use water in an opportunistic way, with immediate leaf rehydration and concomitant photosynthesis increments. Conversely, deep-rooted shrubs (U. airensis) were unresponsive, only recovering photosynthesis with high soil water content. An opportunistic growth response may be disadvantageous to shallow-rooted shrubs in a future climate with extended dry summers and higher probability of rain pulse events. The prominent increase in transpiration rates and plant respiration costs observed during the dry conditions that followed the rain pulse, led to a reduced plant ability to recover after autumn rains. Conclusions The shrubs that naturaly colonized this montado understorey showed contrasting strategies to overcome summer drought, suggesting an efficient mosaic exploitation of seasonal environmental resources. The contribution of these shrubs to total ecosystem CO2 uptake during summer and autumn recovery was 17%. This high contribution implies that shrub density management decisions should consider a carbon balance perspective.
Keywords: Cistus sp; CO2; Eddy-covariance; H2O; Mediterranean; partitioning; Shrubs; Ulex sp; up-scaling

Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins

Influence of secondary compound complementarity and species diversity on consumption of Mediterranean shrubs by sheep - Rogosic, Jozo; Estell, Richard E.; Skobic, Dragan; Stanic, Svjetlana (Applied Animal Behaviour Science, 2007)
Generalist herbivores foraging in chemically diverse grazing ecosystems like the Mediterranean maquis increase intake on mixed diets, suggesting they are more able to meet nutritional needs and avoid toxicosis. Thus, our objectives were to determine how shrub species diversity and complementary interactions between tannins and saponins inﬂuence intake of Mediterranean shrubs by sheep. We conducted four experiments (10 days each) comparing intake of mixtures of Mediterranean shrubs varying in number of species and/or principal class of secondary compound (tannins or saponins) by sheep (n = 12). Sheep consumed more total foliage (P < 0.01) when offered a high-tannin shrub (Pistacia lentiscus; Exp. 1), two high-tannin shrubs (P. lentiscus and Arbutus unedo; Exp. 2), or three high-tannin shrubs (P. lentiscus, A. unedo, and Quercus ilex; Exp. 3) when fed in conjunction with a high-saponin shrub (Hedera helix) than with an equal number of high-tannin shrubs (20.9 g/kg BW versus 16.3 g/kg BW; 28.8 g/kg BW versus 20.8 g/kg BW; and 35.3 g/kg BW versus 26.9 g/kg BW). Likewise, sheep ate more foliage (P < 0.01) of each additional individual shrub (P. lentiscus, A. unedo, and Q. ilex) in the mixture when fed with H. helix than with an equal number of high-tannin shrubs (8.2 g/kg BW versus 5.0 g/kg BW; 13.3 g/kg BW versus 10.7 g/kg BW; and 7.6 g/kg BW versus 5.2 g/kg BW; Exps. 1–3, respectively), suggesting a complementary interaction between tannins and saponins may have occurred. Sheep also appeared to increase total shrub intake as number of shrub species on offer increased, regardless of number of classes of compounds present. Our ﬁndings suggest that secondary compounds in Mediterranean shrubs (tannins and saponins) are complementary. Species diversity also plays an important role in diet selection, as plant species with different types and amounts of nutrients and phytotoxins may affect forage intake and animal production. This knowledge will help livestock producers to capitalize on phytochemical interactions to enhance intake, optimize forage utilization, and ultimately improve performance of browsing ruminant herbivores
Keywords: Biodiversity; Complementarity; Mediterranean maquis; Saponins; Secondary compounds; Sheep; Shrubs; Tannins

Feed blocks as a supplement for goat kids grazing natural Tunisian rangeland during the dry season - Gasmi-Boubaker, A; Kayouli, C; Buldgen, A (ANIMAL FEED SCIENCE AND TECHNOLOGY, 2006)
Two experiments were conducted to investigate the effects of PEG and feed blocks on digestion of shrub species consumed by goats (experiment 1) and kid growth while browsing during the dry season (experiment 2). In experiment 1, in vitro gas production was determined using a rumen fermenter. Six shrub species were incubated separately (Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber, and Viburnum tinus). Effects of polyethylene glycol (PEG 4000) and feed block supply were investigated. In experiment 2, 21 local kids, 18.75 (+/- 1.4) kg body weight (BW) were allowed to browse in shrub-lands and allocated to three treatments in a production trial lasting 147 days (July-December). Control group receive no supplement, whereas the two other groups received either PEG-free (13) or PEG-containing feed blocks (B-PEG). All shrubs were low in crude protein (59-91 g kg(-1) dry matter) but high in total condensed tannins; mean content was 43 g kg(-1) DM (8.8-65) for bound condensed tannin and 205 g kg(-1) DM (10.8-363) for free condensed tannin. Gas volume produced after 24 h differed among shrub species (P < 0.05). V tinus produced the highest volume (77.8 ml g(-1) organic matter) and Q. suber the lowest (35 ml g-1 OM). The mean rate of fermentation was 0.135h(-1) (0.121-0.150 h(-1)). PEG addition increased gas production by 48.5%, volatile fatty acid by 38.4% and organic matter fermented by 41.7% of the mixture of shrubs (P < 0.05). In the practical trial, the use of blocks with and without PEG avoided BW loss of the goats under dry season. While the control group lost 19 g day(-1), the bloc supplemented groups grew at 12 g day(-1) (-PEG) and 24 (+PEG) g day(-1). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: feed blocks; Gas production; Goat; PEG; Shrubs

Feed blocks as a supplement for goat kids grazing natural Tunisian rangeland during the dry season - Gasmi-Boubaker, A.; Kayouli, C.; Buldgen, A. (ANIMAL FEED SCIENCE AND TECHNOLOGY, 2006)
Two experiments were conducted to investigate the effects of PEG and feed blocks on digestion of shrub species consumed by goats (experiment 1) and kid growth while browsing during the dry season (experiment 2). In experiment 1, in vitro gas production was determined using a rumen fermenter. Six shrub species were incubated separately (Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber, and Viburnum tinus). Effects of polyethylene glycol (PEG 4000) and feed block supply were investigated. In experiment 2, 21 local kids, 18.75 (+/- 1.4) kg body weight (BW) were allowed to browse in shrub-lands and allocated to three treatments in a production trial lasting 147 days (July-December). Control group receive no supplement, whereas the two other groups received either PEG-free (13) or PEG-containing feed blocks (B-PEG). All shrubs were low in crude protein (59-91 g kg(-1) dry matter) but high in total condensed tannins; mean content was 43 g kg(-1) DM (8.8-65) for bound condensed tannin and 205 g kg(-1) DM (10.8-363) for free condensed tannin. Gas volume produced after 24 h differed among shrub species (P < 0.05). V tinus produced the highest volume (77.8 ml g(-1) organic matter) and Q. suber the lowest (35 ml g-1 OM). The mean rate of fermentation was 0.135h(-1) (0.121-0.150 h(-1)). PEG addition increased gas production by 48.5%, volatile fatty acid by 38.4% and organic matter fermented by 41.7% of the mixture of shrubs (P < 0.05). In the practical trial, the use of blocks with and without PEG avoided BW loss of the goats under dry season. While the control group lost 19 g day(-1), the bloc supplemented groups grew at 12 g day(-1) (-PEG) and 24 (+PEG) g day(-1). (c) 2005 Elsevier B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: feed blocks; Gas production; Goat; PEG; Shrubs

Assessment of the digestibility of some Mediterranean shrubs by in vitro techniques - Ammar, H.; López, S.; González, J. S. (Animal Feed Science and Technology, 2005)
The nutritive value of some Mediterranean browse species collected in Tunisia was studied on the basis of their chemical composition, in vitro digestibility and fermentation kinetics (gas production technique). The browse species evaluated were Arbutus unedo, Calicotome villosa, Erica arborea, Myrtus communis, Phillyrea angustifolia, Pistacia lentiscus and Quercus suber. Species varied widely in crude protein content (55–221 g/kg DM), condensed tannins (1–360 g/kg DM), digestible dry matter (DM) (523–681 g/kg DM), asymptotic gas production (187–343 ml/g DM) and fractional gas production rate (0.030–0.047 h−1 ). Based on their in vitro digestibility and fermentation kinetics, species could be clustered in two groups of fodder resources, one of medium-high digestibility including the species M. communis, C. villosa, Ph. angustifolia and A. unedo and another group of low digestibility comprising the species P. lentiscus, Q. suber and E. arborea. The in vitro digestibility and gas production parameters were negatively correlated with phenolic compounds, in particular condensed tannins, suggesting that these in vitro techniques can be appropriate for detecting the presence of anti-nutritional substances in shrubs
Keywords: Gas production; In vitro digestibility; Nutritive value; Shrubs; Tannins

Assessment of the digestibility of some Mediterranean shrubs by in vitro techniques - Ammar, H; López, S; González, J S (Animal Feed Science and Technology, 2005)
The nutritive value of some Mediterranean browse species collected in Tunisia was studied on the basis of their chemical composition, in vitro digestibility and fermentation kinetics (gas production technique). The browse species evaluated were Arbutus unedo, Calicotome villosa, Erica arborea, Myrtus communis, Phillyrea angustifolia, Pistacia lentiscus and Quercus suber. Species varied widely in crude protein content (55–221 g/kg DM), condensed tannins (1–360 g/kg DM), digestible dry matter (DM) (523–681 g/kg DM), asymptotic gas production (187–343 ml/g DM) and fractional gas production rate (0.030–0.047 h−1 ). Based on their in vitro digestibility and fermentation kinetics, species could be clustered in two groups of fodder resources, one of medium-high digestibility including the species M. communis, C. villosa, Ph. angustifolia and A. unedo and another group of low digestibility comprising the species P. lentiscus, Q. suber and E. arborea. The in vitro digestibility and gas production parameters were negatively correlated with phenolic compounds, in particular condensed tannins, suggesting that these in vitro techniques can be appropriate for detecting the presence of anti-nutritional substances in shrubs
Keywords: Gas production; In vitro digestibility; Nutritive value; Shrubs; Tannins

In vitro gas production and its relationship to in situ disappearance and chemical composition of some Mediterranean browse species - Gasmi-Boubaker, Aziza; Kayouli, C; Buldgen, A (Animal Feed Science and Technology, 2005)
In vitro gas production of seven species (i.e., Arbutus unedo, Calycotum villosa, Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber) that are widely browsed by goats were measured through 120 h and related to in situ dry matter disappearance (DMD) and chemical composition. Three goats fitted with ruminal cannulae were used for the in vitro and in situ studies. Browses varied in their crude protein (CP: 55–221 g/kg DM) and neutral detergent fibre (360–551 g/kg DM) contents. High levels of total condensed tannins (TCT) were observed in Pistacia lentiscus, and the lowest levels were in Calycotum villosa and Phillyrea angustifolia. The browses varied widely in potential (145.7–224.0 ml/g DM) and fractional rates (0.038–0.075/h) of gas production, and there were differences among species in DMD (P < 0.05). Gas production at 24 h was positively correlated (P < 0.05) with in situ DM disappearance and CP content, but negatively correlated (P < 0.05) to acid detergent lignin (ADL), free condensed tannins (FCT) and TCT contents. The fractional rate of fermentation (μ) was negatively related (P < 0.05) to FCT (r = −0.81) and TCT (r = −0.83), whereas DMD was only related to acid detergent fibre and ADL content. Results support combined use of gas production and in situ techniques to determine the nutritive value of feeds containing phenolic compounds.
Keywords: Gas production; In situ disappearance; Shrubs; Tannins

In vitro gas production and its relationship to in situ disappearance and chemical composition of some Mediterranean browse species - Gasmi-Boubaker, Aziza; Kayouli, C.; Buldgen, A. (Animal Feed Science and Technology, 2005)
In vitro gas production of seven species (i.e., Arbutus unedo, Calycotum villosa, Erica arborea, Phillyrea angustifolia, Pistacia lentiscus, Myrtus communis, Quercus suber) that are widely browsed by goats were measured through 120 h and related to in situ dry matter disappearance (DMD) and chemical composition. Three goats fitted with ruminal cannulae were used for the in vitro and in situ studies. Browses varied in their crude protein (CP: 55–221 g/kg DM) and neutral detergent fibre (360–551 g/kg DM) contents. High levels of total condensed tannins (TCT) were observed in Pistacia lentiscus, and the lowest levels were in Calycotum villosa and Phillyrea angustifolia. The browses varied widely in potential (145.7–224.0 ml/g DM) and fractional rates (0.038–0.075/h) of gas production, and there were differences among species in DMD (P < 0.05). Gas production at 24 h was positively correlated (P < 0.05) with in situ DM disappearance and CP content, but negatively correlated (P < 0.05) to acid detergent lignin (ADL), free condensed tannins (FCT) and TCT contents. The fractional rate of fermentation (μ) was negatively related (P < 0.05) to FCT (r = −0.81) and TCT (r = −0.83), whereas DMD was only related to acid detergent fibre and ADL content. Results support combined use of gas production and in situ techniques to determine the nutritive value of feeds containing phenolic compounds.
Keywords: Gas production; In situ disappearance; Shrubs; Tannins

Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs

Invasión del matorral por Genista hystrix en una dehesa salmantina (España) - Caro Domínguez, Francisco; Sánchez Anta, María Ángeles; Tarazona Lafarga, Teresa (Ecología Aplicada, 2004)
The invasion of Genisto hystricis-Cytisetum multiflori shrubs in a Salamancan "dehesa" (Quercus forest with low density), was studied using permanent quadrat and transect methodology. The results indicate that, of all shrub species, Genista hystrix Lge. is the predominant invading species in this sclerophyllous formation, due to its growth rate and phenomorphology. The overall invasion rate of this shrub in the "dehesa" has been calculated to be approximately 2.26 m 2 per year
Keywords: "dehesa"; Cytisus multiflorus (L'Hèr.) Sweet.; Cytisus scoparius (L.) Link; dynamics; Genista hystrix Lge.; Invasive species; Quercus rotundifolia Lam.; Salamanca; sclerophyllous; Shrubs